EFFICIENCY ALGORITHM OF SEISMIC RAY TOMOGRAPHY IN PROCESSING EXTENSIVE SEISMIC DATA - Troinich, K.; Vyzhva, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Seismic tomography is both a powerful tool for studying Earth’s subsurface and a standard for worldwide geophysics. However, this method has a very sporadic implementation in Ukraine. In order to raise standards of Ukrainian geophysics and in accord with the scientific research into the methodology of dynamic geological and geophysical models for geological objects and processes (the programme being funded by Theoretical and Applied Research Foundation at Kyiv National University) the Department of Geophysics (Institute of Geology) has been developing a methodology for geophysical tomography and lithological inversion. Namely, there have been elaborated a computing algorithm and upgraded software programming to launch seimic ray tomography. To update velocity model there was chosen a simultaneous iterative reconstruction tomography (SIRT) technique. This technique is a modification of algebraic reconstruction tomography (ART) that calculates updating of the velocity model simultaneously using all available rays that cross the model at different angles. Software programmes have been tested in upgraded programming environment and on the computational models. Ray tracing through velocity model is grounded in calculating shortest path tree (SPT) when using network theory. This approach allows calculating ray-paths and travel-times for all rays starting with one source point. It saves a lot of time and resources for performing calculations. Having proved to be a fastest and robustest algorithm for a large amount of data, L-deque was chosen to be an algorithm for building shortest path tree.